Sustainable development at UK universities: an exploratory study into the sustainable management of Nottingham University Business School - Bhal, Sonu (2022)
This research investigates the current state of sustainable development at UK higher education institutions by deducing key themes within recent initiatives. Additionally, the thematic headlines are applied to Nottingham University Business School to assess its degree of sustainability amongst UK universities. The 2030 UN Agenda highlights global targets for development across the world, where universities are identified as key stakeholders in lessening the environmental impacts of current practices, as well as improving the human activity and well-being of students, staff, and the local community. In conducting this research, a systematic literature review was produced to form an in-depth understanding of all relevant literature concerning this topic, via an unbiased and replicable procedure. WebofScience was the sole database utilised to identify the eight relevant studies, from which education, partnerships, and carbon management were deemed the key themes. In synthesising the case study, key data and information was predominantly obtained from reports released by the business school which outlined a variety of initiatives implemented in recent years. The findings demonstrate aspects of all three themes in several strategies, as the school targets improvements in all 17 Sustainable Development Goals. With regard to education, the increased availability of optional sustainability modules at all levels of teaching demonstrates the school’s intent to improve the sustainability skills of students through increased exposure. Additionally, Foodprint Nottingham epitomises the power of partnerships, as the student-run project continues to improve local community wellbeing by providing more affordable food to the least affluent. Lastly, aspects of carbon management are exemplified through building an innovative carbon neutral laboratory, where water saving capabilities and energy efficient features embody a ‘green building’. Overall, it appears the school is successfully incorporating sustainable development, however limitations regarding potential bias in the systematic review along with the unknown agendas and motivations of published university reports somewhat tarnish the reliability of this exploratory analysis. Therefore, future research may include stakeholder interviews for diverse opinions or carbon footprint data for a statistical outlook, to ensure that a comprehensive conclusion on the sustainable management of the school can be formed.